Design IIR Filter on FPGA Technology Combined with Matlab-Simulink Software Tools and Electronic Design Automation Software - Hong Ngan Vo; Xuan Toai Nguyen; Le Thanh Lanh; Le Nam Thoi (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
This paper presents the design of an IIR filter on FPGA technology by combining modeling with automation of digital system design, in order to provide a solution to design and quickly implement the digital signal processing system. The IIR filter is designed by the method of object modeling (Model Based Design) abbreviated as MBD with the help of Matlab and EDA, then experimentally implemented the IIR filter on FPGA technology for a specific problem and achieved quite good results. Through this method, it has helped designers reduce design effort and time, improve economic efficiency, and more importantly, the design is highly flexible, ready to response the new technical requirements of the technology.